Sport science - Haff, G. G. (Strength and Conditioning Journal, 2010)
SPORT SCIENCE IS A VALUABLE PROFESSION THAT IS OFTEN MISUNDERSTOOD. THIS UNIQUE DISCIPLINE CAN EXERT A GREAT IMPACT ON PERFORMANCE DURING SPORTING EVENTS. THIS ROUNDTABLE IS DESIGNED TO CLARIFY SEVERAL KEY CONCEPTS CENTRAL TO UNDERSTANDING WHAT SPORT SCIENCE IS AND HOW TO BECOME A SPORT SCIENTIST.